2016
DOI: 10.1097/gme.0000000000000662
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety as a risk factor for menopausal hot flashes: evidence from the Penn Ovarian Aging cohort

Abstract: Objective The aim of this study was to identify temporal associations of anxiety dimensions with menopausal hot flashes in women progressing through the menopause transition. We hypothesized that associations of both somatic and affective dimensions of anxiety with hot flashes increased in the menopause transition, and that somatic anxiety was an independent risk factor for menopausal hot flashes. Methods Hot flashes, anxiety symptoms, hormone levels and other psychosocial variables were assessed annually fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 44 publications
1
18
0
2
Order By: Relevance
“…Concurring sleep problems and anxiety are frequently observed and their onset and course are interrelated. 100,101 In addition, these disorders are associated with a number of comorbid conditions including depression, [101][102][103] dementia, 5,6 OCD, 104 and hot flashes [105][106][107] (Figure 6). Our results demonstrated that sleep promotion and anxiolytic effects were the major therapeutic benefits expected of valerian (V. officinalis), and this herb could be also useful in treating OCD, cognitive dysfunction, menopausal hot flashes, as well as menstrual problems.…”
Section: Discussionmentioning
confidence: 99%
“…Concurring sleep problems and anxiety are frequently observed and their onset and course are interrelated. 100,101 In addition, these disorders are associated with a number of comorbid conditions including depression, [101][102][103] dementia, 5,6 OCD, 104 and hot flashes [105][106][107] (Figure 6). Our results demonstrated that sleep promotion and anxiolytic effects were the major therapeutic benefits expected of valerian (V. officinalis), and this herb could be also useful in treating OCD, cognitive dysfunction, menopausal hot flashes, as well as menstrual problems.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological distress during the menopausal transition has been associated with history of depression and sexual abuse, body mass index, and stressful life events at midlife [ 29 , 30 ]. Increased prevalence of physical menopausal symptoms, such as hot flushes is also a risk factor [ 29 , 31 ], with estradoil variability potentially enhancing emotional reactivity to psychosocial stress [ 32 ]. However, negative mood change is often attributed to menopause because of broader cultural discourse [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 13 studies also suggests that women with more negative attitudes towards the menopause report more menopausal symptoms, but more prospective studies are needed to determine causality (Ayers et al , 2010). In addition to negative mood, anxiety was also found to be a predictor of VMS even after the adjustment of depression (Freeman and Sammel, 2016). The SWAN study even found that the association with anxiety appeared to be stronger than the association with depressive symptoms (Gold et al , 2006).…”
Section: Discussionmentioning
confidence: 99%